Analysis of Village Financial Statement Presentation in accordance with Government Accounting Standards (SAP) (Case Study in Waluran Village, Waluran District) - Pratama, Ramli; Nurodin, Idang; Indrawan, Andri (Journal of Management, Economic, and Accounting, 2024)
The objectives of this study are as follows: 1) To analyze the presentation of the Financial statements of Waluran Village in accordance with Government Accounting Standards (SAP), 2) To analyze efforts that can be made so that the presentation of the Financial statements of Waluran Village Waluran District is in accordance with Government Accounting Standards (SAP), and 3) To describe the obstacles faced in the presentation of Waluran Village Financial statements in accordance with Government Accounting Standards.  This research is a research that uses qualitative methods using a descriptive approach, using data collection techniques which include: observation, interviews and documentation and using Miles and Huberman model data analysis techniques which include: data collection, data reduction, data presentation and conclusion making. The results of this study show that: 1) The presentation of the Financial statements of Waluran Village, Waluran District, is not fully in accordance with Government Accounting Standards, Waluran Village only presents budget realization reports. While the components of the Financial statements that must be presented according to Government Accounting Standards are budget realization reports, excess budget balance reports, operational reports, cash flow statements, statements of changes in equity and notes to the Financial statements, 2) Efforts that can be made so that the presentation of Waluran Village Financial statements in accordance with applicable accounting standards include: a) Raising the level / competence of human resources,  b) Conducting seminars/training, c) Placing Employees in accordance with their Competence, 3) Constraints in presenting Waluran Village Financial statements in accordance with government accounting standards, which are as follows: a) Relevance or suitability of majors, b) Human resource competence, and c) Lack of information.